Redevelopment and Race : Planning a Finer City in Postwar Detroit - Thomas, June Manning (Book collections on Project MUSE., 2013)
In the decades following World War II, professional city planners in Detroit made a concerted effort to halt the city's physical and economic decline. Their successes included an award-winning master plan, a number of laudable redevelopment projects, and exemplary planning leadership in the city and the nation. Yet despite their efforts, Detroit was rapidly transforming into a notorious symbol of urban decay. In this book, the author takes a look at what went wrong, demonstrating how and why government programs were ineffective and even destructive to community needs. In confronting issues like housing shortages, blight in older areas, and changing economic conditions, Detroit's city planners worked during the urban renewal era without much consideration for low-income and African American residents, and their efforts to stabilize racially mixed neighborhoods faltered as well. Steady declines in industrial prowess and the constant decentralization of white residents counteracted planners' efforts to rebuild the city. Among the issues Thomas discusses in this volume are the harmful impacts of Detroit's highways, the mixed record of urban renewal projects like Lafayette Park, the effects of the 1967 riots on Detroit's ability to plan, the city-building strategies of Coleman Young (the city's first Black mayor) and his mayoral successors, and the evolution of Detroit's federally designated Empowerment Zone. Examining the city she knew first as an undergraduate student at Michigan State University and later as a scholar and planner, the author ultimately argues for a different approach to traditional planning that places social justice, equity, and community ahead of purely physical and economic objectives.